Weaving and Tailoring the Andean Church: Textile Ornaments and Their Makers in Colonial Peru. Issue 1 (20th February 2015) - Stanfield-Mazzi, Maya
Abstract : The first Christian churches were built in the Andes soon after Spaniards arrived. Initially simple structures, they were later remodeled into large stone monuments. Aside from their architectural construction, the furnishing and decoration of these churches was an ongoing project that involved many participants, often under the watchful eye of a parish priest. Art historians have uncovered fascinating cases in which native artists exercised agency in creating works to be displayed in church interiors, many of which expressed Andean as well as Christian beliefs. This scholarship has focused primarily on the art forms of painting and sculpture, which were very visible within the church, especially in cases such as the baptism murals discussed by Ananda Cohen Suarez in this issue. An underappreciated yet equally notable aspect of church decoration was textiles. Throughout the colonial period churches were abundantly adorned with "church clothing, " textile ornaments meant to cover floors, walls, and altars as well as clothe church functionaries and religious statuary. The purchase and maintenance of church textiles consumed the lion's share of annual church budgets.